2017
DOI: 10.1038/s41598-017-04907-y
|View full text |Cite
|
Sign up to set email alerts
|

Distinct brain responses to different inhibitions: Evidence from a modified Flanker Task

Abstract: Whether inhibition is a unitary or multifaceted construct is still an open question. To clarify the electrophysiological distinction among the different types of inhibition, we used a modified flanker paradigm, in which interference inhibition, rule inhibition, and response inhibition were compared to non-inhibition condition. The results indicated that, compared to the non-inhibition condition (1) the interference inhibition condition induced larger negativities during N2 epoch at the frontal region, (2) the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 110 publications
1
37
0
Order By: Relevance
“…However, we did find that conflict processing varied slightly by site. Together these findings are in line with previous P3 research, specifically that the P3 was maximal parietally but the conflict processing effect was maximal frontocentrally (Rietdijk, Franken, & Thurik, 2014;Xie, Ren, Cao, & Li, 2017). This is consistent with prior distinction between the frontal P3a (i.e., attention-switching) and the parietal P3b (i.e., inhibition; Polich, 2007).…”
Section: Aim 1: Impact Of Threat On Cognitive Controlsupporting
confidence: 92%
See 1 more Smart Citation
“…However, we did find that conflict processing varied slightly by site. Together these findings are in line with previous P3 research, specifically that the P3 was maximal parietally but the conflict processing effect was maximal frontocentrally (Rietdijk, Franken, & Thurik, 2014;Xie, Ren, Cao, & Li, 2017). This is consistent with prior distinction between the frontal P3a (i.e., attention-switching) and the parietal P3b (i.e., inhibition; Polich, 2007).…”
Section: Aim 1: Impact Of Threat On Cognitive Controlsupporting
confidence: 92%
“…While the congruence N2 and P3 may index somewhat different aspects of cognitive control (Xie, Ren, Cao, & Li, 2017), studies that have used simultaneous EEG-fMRI (functional magnetic resonance imaging; a measure of hemodynamic activity within the brain that provides high-resolution spatial information about precise regions of the brain involved in particular cognitive processes) have found that the congruence N2 and P3 overlap in terms of associated neural generators. Specifically, across a range of cognitive control paradigms, activation in the dlPFC, anterior cingulate cortex (ACC), and insula have been associated with the N2 and P3, as well as with broader inhibitory control processes (Baumeister et al, 2014;Swick, Ashley, & Turken, 2011;Volpe, Mucci, Bucci, Merlotti, Galderisi, & Maj, 2007).…”
Section: Cognitive and Inhibitory Control Processesmentioning
confidence: 99%
“…Hence, we inferred that although the main informative value of the two types of positive feedback is to keep the selected rule in working memory, when 2PF appears, participants should additionally inhibit the invalid rule that was selected during the first match. The additional inhibition for 2PF might be reflected by the increased P300 ( Roberts et al, 1994 ; Xie et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…While the oddball task has been used extensively to characterize P3 (e.g., Polich and Kok, 1995 ; Polich, 1996 ; Goldstein et al, 2002 ; Conroy and Polich, 2007 ; Wronka et al, 2008 ; HorvĂĄth et al, 2010 ; Höller et al, 2013 ; Verleger and Smigasiewicz, 2016 ), the P3 has also been widely characterized using the Eriksen flanker task (e.g., Hillman et al, 2004 ; Clayson and Larson, 2011 ; Rusnakova et al, 2011 ; Hsieh et al, 2012 ). Furthermore, the flanker task has been used to characterize N2 and is considered a task specifically related to attentional inhibition, a marker of cognitive control (Ridderinkhof and van der Molen, 1995 ; Jonkman et al, 1999 ; Johnstone et al, 2009 ; Purmann et al, 2011 ; Brydges et al, 2014 ; Groom and Cragg, 2015 ; Xie et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%